혼합물 실험 계획법에 의한 압출성형 대체육의 혼합비율 최적화 - 송하영(Ha Young Song); 정윤조(Yun Jo Jung); 조연재(Yeon Jae, Jo); 홍은아(Eun Ah Hong); 구민경(Min Kyung Gu); 석원호(Won Ho Suk); 이준수(Junsoo Lee); 정헌상(Heon Sang Jeong) (한국식품과학회지, 2024)
혼합물 실험 계획법을 이용하여 활성 글루텐, 분리완두단백 및 분리대두단백 첨가 비율을 달리하여 압출성형 대체육을 제조하고 품질특성을 평가하여 쇠고기와 유사한 대체육의 제조조건을최적화하였다. F-test를 통해 유의성을 검정하였으며, 경도, 검성, 절단력, 조직잔사지수 및 수분흡착지수는 quadratic 모델로, 압축력, 수분용해지수 및 단백질 소화율은 linear 모델이 선택되었다(p<0.05). 활성 글루텐 첨가량이 많을수록 경도, 검성, 압축력, 절단력 및 조직잔사지수와 같은 물리적 특성은 증가한 반면, 분리완두단백 첨가량이 증가할수록 낮아졌다. 혼합비 최적화 결과 대조구인 쇠고기와 유사한 예측 반응에 대한 만족도는 0.7567 이었으며, 활성 글루텐 19.81%, 분리완두단백 25.71% 및 분리대두단백 24.48%로 나타났다. 최종 재료 배합비로 압출성형 대체육을 제조할 경우 쇠고기와 유사한 대체육 제조가 가능할 것이라판단된다. This study performed a mixture design to manufacture extruded meat analog by mixing gluten, isolated pea protein, and isolated soy protein, and evaluated quality characteristics to optimize ingredient formulation for meat analogs similar to beef. F-test indicated that a quadratic model was appropriate for evaluating hardness, gumminess, cutting force, the integrity index, and the water absorption index, whereas a linear model was optimal for assessing compression force, the water solubility index, and protein digestibility (p<0.05). Increasing gluten content resulted in increased hardness, gumminess, compression force, cutting force, and integrity index. Conversely, these properties decreased with increasing isolated pea protein content. The D-value for the optimum formulation, which closely resembled that for beef was 0.7567, with composition of 19.81% gluten, 25.71% isolated pea protein, and 24.48% isolated soy protein. This optimized ingredient formulation is expected to yield meat analogs with characteristics similar to those of beef, providing a foundation for producing high-quality meat analogs. KCI Citation Count: 0